O que é macumba para os alunos do 7° ano de uma escola estadual de tempo integral na zona leste de Manaus/AM - Manoel Vitor Barbosa Neto (Das Amazônias)
This article aims to reflect on religious intolerance against Afro-Brazilian religions based on an experience report in a school context, in a Religious Education class, which addressed the word “macumba”. In this context, we sought to understand the students’ perception of the term, and then present the possible etymologies of the expression, as well as to point out how the colonial process, racism and the imposition of Christianity with its dualistic worldview (good and evil) shaped the negative understanding of the term “macumba” and, consequently, of Afro-Brazilian religions. To this end, in addition to the report, a bibliographical research was also carried out on religious intolerance, specifically against Afro-Brazilian religions. Finally, this article concludes the need to study Afro-Brazilian religions in Religious Education and collaborate in the deconstruction of these negative perceptions that express racism in Brazilian society.